Changes in N, K, and Fatty Acid Composition of Black Cumin Seeds Affected by Nitrogen Doses under Supplemental Potassium Application - Zehra Aytac; Nurdilek Gulmezoglu; Tugce Saglam; Engin Gokhan Kulan; Ugur Selengil; Halit Levent Hosgun (Journal of Chemistry)
This study was carried out to determine the efficiency of nitrogen (N) doses (0, 30, 60, and 90 kg N ha−1) under supplemental potassium (K) application (50 kg K2O ha−1) on black cumin in 2011 and 2012. The results showed that increased N levels resulted in increasing seed yield and N and K contents in seed, while oil content decreased. The seed yield and oil yield were peaked at the doses of 60 kg N ha−1 and 50 kg K ha−1. An increase in N doses caused a reduction in oil content regardless of K supply. Saturated fatty acids and oleic acid were slightly increased by K application, while minor changes in linoleic acid were detected. It was concluded that 60 kg N ha−1 with supplemental K application should be advised for enhancement in seed yield, oil yield, and N and K contents in seeds of black cumin without significant changes in fatty acid composition.